Mental health in Northern Malawi : a cultural perspective - Smyth, Karen M. (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Psychiatry, 2002)
This thesis seeks to address a theoretical question: What is the experience of people with a mental disturbance, when they are introduced to a health care system which is ontologically distinct from their own cultural beliefs about health? This question was addressed in the context of a recently established biomedically orientated mental health service in Northern Malawi. Mental disturbance is predominately treated by traditional healers in this region. Two parallel studies were conducted; a longitudinal study which explored the explanation’s patients in the mental health service held regarding their mental disturbance and a study which focussed on traditional healers in the extant healing system.
Keywords: Psychiatry, Ph.D.; Ph.D. Trinity College Dublin